New monoclonal/bi-specific antibodies: Reshaping transfusion medicine beyond replacement. (April 2019) - Goubran, Hadi; Goubran, Mariam; Seghatchian, Jerard; Burnouf, Thierry
Abstract: Since the first successful transfusion in 1818, Transfusion Medicine has evolved significantly. The advent of plasma fractionation and availability of recombinant products allowed for precision replacement therapy to treat many hematological conditions, such as hemophilia, thrombotic thrombocytopenic purpura, and hereditary angioedema. A deeper understanding of the pathophysiology underlying those conditions along with the development of safer monoclonal and bispecific antibodies is now offering safe and effective alternatives to the simple conventional approach of replacing a missing plasma protein. Many biologicals are already in wide clinical use in areas such as rheumatology, gastroenterology, and medical oncology. The introduction of novel therapeutic antibodies within the realm of Transfusion Medicine will likely reshape the field and challenge the role of local blood establishments as the gate-keepers of such therapies.